Composição Corporal e Puberdade de Leitoas Alimentadas com Níveis Alto e Baixo de Proteína na Dieta - Budiño, Fábio Enrique Lemos [UNESP]; De Mello Kessler, Alexandre; Bernardi, Mari Lourdes (My University, 2001)
With the aim of altering body composition, diets with different protein levels (12 and 18 CP) were offered to breeding gilts from 100 to 221 days of age. During this period, body weight, backfat thickness, oestrus manifestation, characteristics of reproductive tract and nitrogen balance were evaluated. Nitrogen balance was measured during two metabolism trials (at 136 and at 201 days of age). In both trials, gilts fed 18% CP showed higher nitrogen intake, retention and excretion and higher plasmatic and urinary urea levels (P<0.001). The efficiency of nitrogen utilization was not influenced by dietary protein level (P>.05). The low-protein diet reduced by 48% the excretion of nitrogen. Gilts fed 12% CP showed a greater backfat change (7.4 mm) than those fed 18% CP (4.5 mm), between 100 and 207 days of age (P<.02). Body weight, uterine weight, uterine horns length and number of corpora lutea were not influenced by the level of dietary protein. The rate of oestrus detection, up to 25 days after male exposure, was similar to females receiving 12% (71%) and 18% CP (75%). The protein level affected body composition without altering body weight, onset of puberty and characteristics of the reproductive tract, suggesting that a low-protein diet can be used as an strategy to increase the backfat thickness of breeding gilts.
Body Composition and Puberty of Gilts Fed Low and High Protein Diets
Keywords: Gilts; Metabolism; Nitrogen excretion; Protein; Reproduction